2007
DOI: 10.1200/jco.2006.07.7800
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Institutional Reciprocal Validation Study of Computed Tomography Predictors of Suboptimal Primary Cytoreduction in Patients With Advanced Ovarian Cancer

Abstract: Purpose Identify features on preoperative computed tomography (CT) scans to predict suboptimal primary cytoreduction in patients treated for advanced ovarian cancer in institution A. Reciprocally cross validate the predictors identified with those from two previously published cohorts from institutions B and C. Patients and Methods Preoperative CT scans from patients with stage III/IV epithelial ovarian cancer who underwent primary cytoreduction in institution A between 1999 and 2005 were retrospectively revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
128
2
13

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(144 citation statements)
references
References 31 publications
1
128
2
13
Order By: Relevance
“…Previous investigators assessing the utility of preoperative CT scan in this setting have retrospectively identified different radiologic predictors. [14][15][16][17][18] Axtell et al's analysis of 65 patients showed diaphragm disease and large bowel mesentery implants to be significant factors. 15 Dowdy et al's review of 89 patients found diffuse peritoneal thickening to be the only variable significantly associated with suboptimal debulking which is comparable to our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous investigators assessing the utility of preoperative CT scan in this setting have retrospectively identified different radiologic predictors. [14][15][16][17][18] Axtell et al's analysis of 65 patients showed diaphragm disease and large bowel mesentery implants to be significant factors. 15 Dowdy et al's review of 89 patients found diffuse peritoneal thickening to be the only variable significantly associated with suboptimal debulking which is comparable to our study.…”
Section: Discussionmentioning
confidence: 99%
“…These scores were added together for a score of 0 to 10 which was compared to the surgical results. [14][15][16]22,23 Blood samples for measurement of CA125, within four weeks prior to surgery. CA125 was assessed by enzyme immunoassay (Roche E170) using a sandwich method with chemoluminescence.…”
Section: Pre-operative Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This modality of assessment, in experienced hands, has been shown to have PPV of 87% and NPV of 100% [20][21][22]. However, laparoscopic assessment requires an experienced surgical team and laparoscopic resources.…”
Section: Discussionmentioning
confidence: 99%
“…Дополнительные возможности ранней диагно-стики РЯ появились при появлении принципиально нового подхода -идентификация различных сое-динений, участвующих в процессах канцерогенеза [1,[12][13][14], в том числе, протеолитических ферментов (протеаз), которые принимают участие практически во всех звеньях канцерогенеза -пролиферации, диф-ференциации, ангиогенезе, инвазии, метастазирова-нии [4,[15][16][17][18].…”
Section: литературный обзорunclassified